The Effect of a Holistic Approach-Based Tennis Training Model on Improving Forehand and Backhand Stroke Skills - Jatra, Rices; Yulianti, Mimi; Firmansyah, Swara Ilham; Okramahenza, Muhammad Tegar (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to measure the effect of a holistic approach-based tennis training model on improving Backhand and Forehand stroke skills in junior tennis athletes. The holistic training model used in this study emphasises the integration of technical, mental, and physical aspects simultaneously, in contrast to conventional models that focus more on mechanical repetition of techniques. Materials and Methods. This study used an experimental design with 11 participants who were divided into two groups: an experimental group that participated in training based on a holistic approach and a control group that used a conventional training model. Data were collected through pre-test and post-test tests to measure Backhand and Forehand technique skills. The average pre-test score for Forehand was 15.27, while the post-test increased to 17.18. For Backhand, the pre-test average was 15.45, and the post-test average was 16.73. Statistical analysis was performed with t-test to compare the difference in pre-test and post-test scores. Results. The results showed an increase in Forehand and Backhand scores after the training, but the changes were not statistically significant. Nonetheless, the holistic training model showed a positive impact on skill improvement with a difference (D) for Forehand of 35.00 and for Backhand of 22.00. The variation in results on the Forehand was greater with a post-test standard deviation of 3.488, while the Backhand showed less variation with a post-test standard deviation of 3.133. The inconsistency of these results suggests that despite the improvement in skills, the effectiveness of the holistic training model still requires further testing. Conclusions. The holistic approach-based training model is more effective in improving junior tennis skills compared to conventional methods, especially on Forehand technique. However, to achieve more consistent results, this approach needs to be further customised. Further research is recommended to explore the long-term benefits of this training model and its applicability in other sports.